Study of Inflation in North Sulawesi: An Error Correction Model (ECM) - Watuseke, Anes (CV. Rayyan Dwi Bharata, 2024)
This research was conducted to determine the influence of economic variables that can explain changes or variations in the inflation rate on the Consumer Price Index (CPI) as the dependent variable. The explanatory (independent) variables used as controls are SBI, nominal interest rate spread (SBI) and the value of the rupiah against the US dollar. Based on these results, according to the specific objectives of the equation II model, it is recommended that economic actors can use the SBI interest rate spread as an indicator of variations in the CPI inflation rate at 8 and 12 month intervals, provided that the level of explanation obtained does not yet show an optimal value.